Evaluating the performance of lateral flow devices for total aflatoxins with special emphasis on their robustness under sub-Saharan conditions - Cvak, B.; Warth, B.; Atehnkeng, J.; Parich, A.; Moritz, A.; Sulyok, M.; Krska, R. (MDPI, 2021)
As aflatoxins are a global risk for humans and animals, testing methods for rapid on-site screening are increasingly needed alongside the standard analytical laboratory tools. In the presented study, lateral flow devices (LFDs) for rapid total aflatoxin screening were thoroughly investigated with respect to their matrix effects, cross-reactivity, their performance under harsh conditions in Sub-Saharan Africa (SSA), and their stability, as well as when compared with liquid chromatography-tandem mass spectrometry (LC-MS/MS). To analyze the matrix effects, qualitative test kits offering a certain cutoff level were used to screen different nut samples. In addition, these tests were challenged on their cross-reactivity with 230 fungal toxins and metabolites. Furthermore, the resulting measurements performed under harsh tropical conditions (up to 38.4 °C and 91% relative humidity) in SSA, specifically Burkina Faso and Mozambique, were compared with the results from a well-established and validated LC-MS/MS-based reference method. The comparison of the on-site LFD results with the reference method showed a good agreement: 86.4% agreement, 11.8% non-agreement, and 1.8% invalid test results. To test the robustness of the cutoff tests, short- and long-term stability testing was carried out in Mozambique and Nigeria. For both experiments, no loss of test performance could be determined. Finally, a subset of African corn samples was shipped to Austria and analyzed under laboratory conditions using semiquantitative aflatoxin tests. A good correlation was found between the rapid strip tests and the LC-MS/MS reference method. Overall, the evaluated LFDs showed satisfying results regarding their cross-reactivity, matrix effects, stability, and robustness.